Pengaruh Tekanan Anggaran Waktu Dan Pemahaman Standar Audit Terhadap Audit Judgment Pada Kantor Akuntan Publik Jakarta Selatan - Oliv Sevtia Wardani; Eko Cahyo Mayndarto; Desyi Erawati (Universitas Veteran Bangun Nusantara, 2025)
Auditing holds significant importance within both business and finance, aiming to deliver an impartial assessment regarding the accuracy of an organization's financial reports. As the call for greater transparency and responsibility increases, the function of auditors becomes essential. A key element that impacts the quality of audits is the auditor's judgment, specifically their capability to make suitable and unbiased choices throughout the auditing process. During audits, auditors frequently encounter a variety of obstacles that can influence their judgment. One major obstacle is the pressure of time constraints. Similarly important is the comprehension of auditing standards. Auditors who deeply understand these standards are more inclined to correctly and suitably implement auditing principles. This study was undertaken to explore how time budget pressure and comprehension of auditing standards affect audit judgment at a public accounting firm in South Jakarta. It is classified as quantitative research. The study sample comprised 70 individuals chosen through purposive sampling. Data were analyzed using multiple regression techniques, with hypothesis testing performed via F-tests and t-tests. The findings from the F-test indicate that the research variables are appropriate for the model (Sig. = 0. 000). Results from t-tests confirm that both time budget pressure and understanding of audit standards have a significant impact on audit judgment at the South Jakarta Public Accounting Firm (Sig. = 0. 000). The overall combined effect of time budget pressure and understanding auditing standards on audit judgment measures at 62. 2%.